2016
DOI: 10.1186/s12967-016-0791-2
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma and immunotherapy bridge 2015

Abstract: Table of contentsMELANOMA BRIDGE 2015KEYNOTE SPEAKER PRESENTATIONSMolecular and immuno-advancesK1 Immunologic and metabolic consequences of PI3K/AKT/mTOR activation in melanomaVashisht G. Y. Nanda, Weiyi Peng, Patrick Hwu, Michael A. DaviesK2 Non-mutational adaptive changes in melanoma cells exposed to BRAF and MEK inhibitors help the establishment of drug resistanceGennaro Ciliberto, Luigi Fattore, Debora Malpicci, Luigi Aurisicchio, Paolo Antonio Ascierto, Carlo M. Croce, Rita ManciniK3 Tumor-intrinsic beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…23 The relationship between the efficacy and toxicity of immunotherapy is interesting. A study 24 found that patients with advanced melanoma who had immunerelated adverse events treated with anti-PD-1 had a higher response rate. In addition, the risk of irAEs in ICIs seemed to be dose-dependent, but no cumulative toxicity of longterm exposure to anti-PD-1 was observed.…”
Section: Discussionmentioning
confidence: 99%
“…23 The relationship between the efficacy and toxicity of immunotherapy is interesting. A study 24 found that patients with advanced melanoma who had immunerelated adverse events treated with anti-PD-1 had a higher response rate. In addition, the risk of irAEs in ICIs seemed to be dose-dependent, but no cumulative toxicity of longterm exposure to anti-PD-1 was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The revival of therapeutic affectation of the immune system has revolutionized patient outcome in many solid tumors in the last few years, in particular in melanoma [25]. This Immunotherapy approach is currently also being evaluated in STS.…”
Section: New Therapeutic Avenuesmentioning
confidence: 99%
“…The eukaryotic single-celled pathogens such as the pathogenic fungus Cryptococcus neoformans and the protozoan parasites Leishmania major and donovani [125] secrete exosomes, which may influence the host immune system. The second group is exosomes released by mammalian cells infected with pathogenic bacteria, prion protein, and viruses [126,127]. Previous studies have reported that bacteria can secrete outer membrane vesicles; fungi and eukaryotic parasite can also secrete extracellular vesicles [128].…”
Section: Exosomes Role In Normal and Cancer Cellsmentioning
confidence: 99%